Two rare cases of porphyria. - Sultan, S.T.; Sultan, J. (European Journal of Pediatric Dermatology, 2008)
Porphyrias are rare metabolic disorders of heme biosynthesis that result from a deficiency of enzymes involved in the heme biosynthesis with a pathological accumulation and measurable excretion of porphyrins and/or porphyrin precursors. We are reporting two patients, one with congenital erythropoietic porphyria and the other with hepatoerythropoietic porphyria. Both these disorders are very rare and can present with similar clinical features.